2021
DOI: 10.1186/s40850-021-00079-5
|View full text |Cite
|
Sign up to set email alerts
|

White-nose syndrome-related changes to Mid-Atlantic bat communities across an urban-to-rural gradient

Abstract: Background White-nose Syndrome (WNS) has reduced the abundance of many bat species within the United States’ Mid-Atlantic region. To determine changes within the National Park Service National Capital Region (NCR) bat communities, we surveyed the area with mist netting and active acoustic sampling (2016–2018) and compared findings to pre-WNS (2003–2004) data. Results The results indicated the continued presence of the threatened Myotis septentriona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…The changes in Perimyotis subflavus acoustic activity we observed were consistent with our predictions and similar to patterns in northern WNSpositive regions of eastern North America. Previous studies found a decrease in acoustic activity following WNS detection (Ingersoll et al 2013, Nocera et al 2019, Deeley et al 2021. A similar trend in population decline was reported for the federally threatened Myotis septentrionalis following WNS detection in the same WNS-positive region in Georgia where our study occurred (Grider 2020).…”
Section: Discussionsupporting
confidence: 87%
“…The changes in Perimyotis subflavus acoustic activity we observed were consistent with our predictions and similar to patterns in northern WNSpositive regions of eastern North America. Previous studies found a decrease in acoustic activity following WNS detection (Ingersoll et al 2013, Nocera et al 2019, Deeley et al 2021. A similar trend in population decline was reported for the federally threatened Myotis septentrionalis following WNS detection in the same WNS-positive region in Georgia where our study occurred (Grider 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Gaining information about the natural history of local bat species and determining, observationally and experimentally, the fine‐scale mechanisms that shape their activity could assist the development of management practices that involve bats. Not surprisingly based on earlier regional bat survey assessments (Deeley et al, 2021), we found big brown/silver‐haired bats to be the most active species group in our study area. Our hypothesis that soybean HIPVs affect bat activity was not supported by our results; however, the lack of significant differences in activity does not prove a lack of effect (Alderson, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…Two of the Myotis spp. included in the identification parameters (northern long‐eared and Indiana myotis) were not detected and are largely extirpated from eastern Maryland (Deeley et al, 2021). Bat species was a significant predictor of activity (χ 2 = 2678.4, df = 6, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations